1987
DOI: 10.3382/ps.0660795
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex and Cell Cooperation

Abstract: We have studied the role of major histocompatibility antigens on cell cooperation in the immune response of the chicken. In the 1970's, shortly after the initial discoveries in the mouse, we demonstrated that the T cell-B cell interaction is major histocompatibility complex (MHC)-dependent in the chicken and requires at least one haplotype identity between the collaborating cells. Later, by using MHC-congenic and MHC-recombinant lines, we demonstrated that the T-B cell interaction in antibody response is MHC-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Progesterone significantly increased the frequencies of cells in the mucosal epithelium in the infundibulum and magnum, whereas DES had no significant effect (Fig. 8) (Ewert et al, 1980), and it is closely associated with the function of helper cells in immune responses (Nordskog et al, 1987;Vainio et al, 1987;Alberts et al, 1994). In this study, (Chen et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Progesterone significantly increased the frequencies of cells in the mucosal epithelium in the infundibulum and magnum, whereas DES had no significant effect (Fig. 8) (Ewert et al, 1980), and it is closely associated with the function of helper cells in immune responses (Nordskog et al, 1987;Vainio et al, 1987;Alberts et al, 1994). In this study, (Chen et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…When hybridized to mRNA from human B-LCLs, the C12.3 probe also detected an abundant transcript of 1.3 kb (D. Piatier-Tonneau, personal communication), suggesting the existence of a human gene highly homologous to C12. 3. From a cDNA library of the human B-LCL JY, 105 recombinants were screened under conditions of medium stringency and 115 positive clones were detected; 10 positive clones were isolated, and 1 of them, H12.3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…B-F and B-L antigens are homologous to the mammalian MHC class I and class II molecules, respectively, whereas B-G antigens, found in the erythroid lineage only, have no known mammalian counterpart (2). The chicken B complex has been shown to control the same wide range of immunological reactions in this species as in mouse or man (3). In addition, association between MHC haplotypes and certain biological traits have been demonstrated more convincingly in the chicken than in mammals, in part because of the availability of many outbred chicken populations submitted to deliberate selection.…”
mentioning
confidence: 99%
“…Thus, the current results suggest that DES increases immunocompetent cells in the estrogen target organs, but not in the non-target organs. It was reported that MHC class II molecules are expressed in macrophages, fibroblast-like cells in the ovary and oviduct, activated T and B cells (Ewert et al, 1980 ;Vainio et al, 1987). In the estrogen target organs, DES might stimulate the expression of MHC class II molecules or the production of some factors, like macrophage colony-stimulating factors, that induced MHC class II+ cells.…”
Section: Discussionmentioning
confidence: 99%